Comparison of microwave-assisted hydrodistillation with the conventional hydrodistillation method in extraction of essential oil - Dilaeleyana, Abu Bakar Sidik (2010)
The Basil (Ocimum basilicum) essential oil was a significant interest as a new high-value essential oil especially in pharmaceutical,aromatherapy aid and cosmetics industries which give large opportunities for global marketing. Traditional extraction method Hydodistillation (HD) used to obtain essential oil have several drawbacks which are longer time consuming,have low extraction yields,and higher operational costing.At present the most appropriate technique to improve the quality of essential oil was by using Microwave assisted Hydrodistillation (MAHD) which able to overcome the drawbacks like mentioned above is introduced.This study obtained to identify the effect of the extraction time, yield and composition of Basil essential oil for HD and MAHD.Ratio of Basil and water used was 1:8 were placed in the HD and MAHD setup.The essential oil components were identified by using GCMS.The result shows MAHD can obtained higher yield at lowest extraction time due to more efficient heat transfer involved with microwave. The dominated compound was Methyl cinnamate (34.38% and 66.26%) an oxygenated compound for both HD and MAHD.As a conclusion MAHD obtained greater yield with shorter time and high percentage of oxygenated compounds compared with HD. Furthermore MAHD shows a good alternative method to produce essential oil of Basil.